Effect of Magnesium Doping on Hydration Morphology and Mechanical Property of Calcium Phosphate Cement Under Non‐Calcined Synthesis Condition. Issue 6 (28th February 2013) - Yu, Tao; Ye, Jiandong; Zhang, Ming
Abstract : In this study, magnesium (Mg) was doped into the non‐calcined amorphous calcium phosphate (ACP) via mechanochemical route, and the as‐prepared non‐calcined ACP was used to form a novel hydration system. In this novel hydration system, the effects of Mg doping on the hydration reaction and mechanical property of cement were studied. The incorporation of Mg into the hydration product was confirmed by X‐ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM). The results showed that Mg doping had a significant influence on the nucleation and subsequent growth of apatite crystals. With the Mg doping, the size of hydration crystals was refined, and induced a denser curing body after setting. With the increasing density, the mechanical property of cement was improved effectively. This work explored the inhibiting effect of Mg ions on the nucleation and subsequent growth of apatite under the non‐calcined condition.